1990
DOI: 10.2337/diacare.13.7.725
|View full text |Cite
|
Sign up to set email alerts
|

Fish Oil–Induced Changes in Apolipoproteins in IDDM Subjects

Abstract: The aim of this study was to examine the effect of Max EPA (a commercially available fish oil preparation) on serum cholesterol lipoproteins and apolipoproteins in insulin-dependent diabetic (IDDM) men with dosages that were likely to be acceptable to patients. Twenty-two male IDDM patients aged 20-41 yr, 6 of whom had retinopathy, were recruited from the Royal Perth Hospital diabetic clinic. After screening, subjects were divided into three groups. Six of the subjects without retinopathy were randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Specifically, our findings question the efficacy of n-3PUFA supplementation for the treatment and management of T1D and its associated complications. Our data support previous studies conducted in T2D patients [28][29][30][31][32] and provide new insight within the context of T1D [13][14][15][16][17][18]. This is the first study to comprehensively assess the impact of n-3PUFA supplementation on vascular health in subjects with T1D.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, our findings question the efficacy of n-3PUFA supplementation for the treatment and management of T1D and its associated complications. Our data support previous studies conducted in T2D patients [28][29][30][31][32] and provide new insight within the context of T1D [13][14][15][16][17][18]. This is the first study to comprehensively assess the impact of n-3PUFA supplementation on vascular health in subjects with T1D.…”
Section: Discussionsupporting
confidence: 88%
“…Dietary recommendations for people with and without diabetes currently advocate increased consumption of foods rich in n-3PUFA but do not recommend n-3PUFA supplementation [12]. However, the evidence underpinning these recommendations for people with diabetes is limited exclusively to people with T2D as very few RCTs have examined the impact of n-3PUFA supplementation on vascular or metabolic outcomes in T1D [13][14][15][16][17][18]. Further, most RCTs in T1D are confounded by short duration supplementation, low n-3PUFA dose, and failure to control for pretreatment fatty acid profile status.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1800-mg group LDL cholesterol increased during EPA-E supplementation, as found by others (21,49). Concentrations of apoB were unaffected.…”
Section: Effects Of Low-dose Epa-e In N1ddmsupporting
confidence: 73%
“…Fish oils and n-3 fatty acids Fish oils or n-3 fatty acids have been found able to reduce plasma triglycerides and VLDL concentrations in the diabetic population (Mori et al, 1990;Rillaerts et al, 1989;Popp-Snijders et al, 1987). One study also observed improved blood rheology when 2.7 g of sardine oil was consumed daily (Kamada et al, 1986).…”
Section: Trans-isomer Fatty Acidsmentioning
confidence: 99%